Increase of Effectiveness of Economy Management in Municipalities (through the example of Energy Conservation) - Danilina, Elena Ivanovna; Chebotarev, Vladimir Evgenevich; Reznikova, Olga Sergeevna; Gorelov, Dmitry Vladimirovich (International Review of Management and Marketing, 2016)
Provision of competitiveness and financial soundness of fuel and energy complex, increase of energy efficiency of economic sectors is one of priority lines of municipal politics development. In this article we attempt to analyse energy efficiency at the level of municipalities. The author has formed criteria and presented a method of express analysis based on ranking score of economy and energy potential of a particular territory. This method was tested when analysing municipal economy of one of the most energy-critical regions of the Russian Federation – the Lipetsk Region. The conducted research allowed to detect main means of increasing the efficiency of municipality economy management. The obtained results can be used in municipality management of various regions, especially if there is similarity to the Lipetsk Region by main groups of criteria. Keywords: energy efficiency, economy of municipalities, method of express analysis, economy and energy potential JEL Classifications: L97, R19, Q48, O13